Health seeking behaviour and factors affecting it among oral cancer patients seeking radiotherapy at a regional cancer centre: a retrospective study - Pradhan, Somen Kumar; Gupta, Shubhra Agrawal; Shrivastava, Neha; Verma, Nirmal; Dixit, Srishti; Panda, Prem Sagar (International Journal Of Community Medicine And Public Health, 2018)
Background: In spite of the progress in therapeutic science, the mortality among patients with Oral cancer is still high when compared to other cancers. However, early diagnosis and treatment are still key to improve prognosis, if a correct diagnosis is made at the initial stage of the disease. The objective of this study is to assess the health seeking behaviour and factors affecting it among oral cancer patients seeking radiotherapy at Regional cancer centre, Dr. B.R. Ambedkar Hospital, Raipur. Methods: This hospital based cross sectional study was conducted in Regional cancer centre, Dr. B.R. Ambedkar Memorial Hospital, Raipur. Data was collected from previous patient records and by interview method regarding demographic details and health seeking behaviour including various delays in presentation of the study subjects. Results: The most common primary presenting complaint among the study subjects was Ulcer (61.59%) followed by Mass (33.02%). The majority of the subjects sought care at Private hospitals (41.72%) followed by government public health care facilities (33.11%) as first health care provider. Among clinic-epidemiological factors, place of residence (p=0.001), distance from RCC, Raipur (p=0.035), Socio-economic status (p=0.01) and initial healthcare provider (p=0.027) were found to be significantly associated with delay in diagnosis and treatment of oral cancer. Conclusions: The patient health seeking behavior can be improved by proper health education and increasing accessibility to primary health care.